IDENTIFICATION OF DYNAMICS LOADS AND A FATIGUE LIFE PREDICTION OF A RAILWAY CRANE LOAD-BEARING STRUCTURE (Perner's Contacts, 2010)
The aim of the paper is to present briefly some results of realized analysis of loadbearing steel structure loads of special railway crane PKP 25/20i which was utilized in some specific ad relatively hard working conditions. The next aim is describing one of possible ways of an identification of stochastically loaded mechanically structures. The purpose of this approach is to find an algorithm of a forecasting control of their working in real working conditions. Virtual models of the structure were be used in an analysis of acting working dynamics loads influence to be able to forecast fatigue life of load-bearing part of the crane jib.
Keywords: working conditions; identification of dynamics loads; fatigue life; load-bearing structure; railway crane